2016
DOI: 10.11648/j.ijaas.20160204.15
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Drought on Lignin Content and Digestibility of Tifton-85 and Coastal Bermudagrass (<i>Cynodon dactylon</i> L.) Hays Produced in Georgia

Abstract: Digestibility of "Tifton 85" Bermudagrass has been noted to be higher than most other Bermudagrass cultivars. However, the superior digestibility of Tifton-85 has not been verified based on samples from producers, nor is it known how water availability might affect this comparison. Recent past weather conditions in Georgia allowed this comparison. Much of Georgia was in severe drought in 2007 and 2008. In contrast, there was less/no drought in 2006 and 2009. In each of these years, producers submitted a substa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…It is well-known that plant cells change cell wall composition to adapt to abiotic stresses, such as salt and drought stress [ 38 ]. The study using bermudagrass Tifton-85 showed that the lignin content was increased under drought conditions [ 39 ], and greater lignin content in the xylem improves resistance to drought stress due to cell wall deposition [ 38 , 40 ]. Although the molecular mechanism for changes in cell wall dynamics by salt or drought stresses is unclear, the chemical reaction requires ROS to crosslink with phenolics [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that plant cells change cell wall composition to adapt to abiotic stresses, such as salt and drought stress [ 38 ]. The study using bermudagrass Tifton-85 showed that the lignin content was increased under drought conditions [ 39 ], and greater lignin content in the xylem improves resistance to drought stress due to cell wall deposition [ 38 , 40 ]. Although the molecular mechanism for changes in cell wall dynamics by salt or drought stresses is unclear, the chemical reaction requires ROS to crosslink with phenolics [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Under mild and mild/severe drought, the content of oleanolic acid and betulin increased in Betula platyphylla [96] and level of triterpenoid glycyrrhizin in Glycyrrhiza glabra [97]. The lignin content was increased in bermudagrass Tifton-85, which is a variety of Cynodon dactylon L., under drought conditions [98]. The flavonoids content was enhanced under stress conditions and high-water deficit conditions improved the medicinal properties of Labisia pumila [99].…”
Section: Drought Stress and Secondary Metabolitesmentioning
confidence: 98%